KAJIAN KOMPETENSI LEMBAGA LITBANG BIDANG INDUSTRI TRANSPORTASI DALAM KEMITRAAN - Agus Santoso (Pusbindiklat - LIPI, 2010)
The existence of a number of R & D institutions in transport, thus far the R & D not been widely used by industry or stakeholders so that the competence of R & D institutions often questionable. Then the efforts of partnership being forged between R & D institutions with limited transportation industry human resource development, utilization of facilities and infrastructure R & D and form partnerships that are not formal. So that has not produced a breakthrough technology that can be used commercially and has values competitiveness. It required leadership R & D institutions are not only a scientist but also well-spirited entreprenour, competence for R & D institutions have a bargaining position in science and technology independence. Thus the expected competence of R & D institutions in the future to realize the BSN (Large Significant and Real).